2021
DOI: 10.3390/agriculture11020133
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield and Quality of Winter Wheat Depending on Previous Crop and Tillage System

Abstract: The effects of previous crops (soybean (Glycine max (L.) Merr.) and winter oilseed rape (Brassica napus L. ssp. oleifera Metzg)), as well as of conventional tillage (CT) and no-tillage (NT), on yield and some quality parameters of winter wheat (Triticum aestivum L.) grain were evaluated based on a four-year field experiment. Wheat was grown in a four-field crop rotation: Soybean—winter wheat—winter oilseed rape—winter wheat. The study revealed that growing winter wheat after soybean, compared to its cultivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
2
6
0
9
Order By: Relevance
“…The nutrient requirements and preferences of the preceding crop, the way it is fertilized, and the proportion of the same or similar crops (such as cereals) in the crop rotation have an impact on the nutrient supply in the soil, the occurrence of pathogenic organisms, and ultimately grain yield [ 54 , 55 , 56 ]. A comparison between soybean and winter rape showed that soybean is a more suitable preceding crop for wheat than winter rape, significantly increasing the grain and straw yield of wheat [ 57 ]. Unfortunately, in the Czech Republic, winter rape is the dominant crop preceding wheat due to the high demand from the food and energy industries.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient requirements and preferences of the preceding crop, the way it is fertilized, and the proportion of the same or similar crops (such as cereals) in the crop rotation have an impact on the nutrient supply in the soil, the occurrence of pathogenic organisms, and ultimately grain yield [ 54 , 55 , 56 ]. A comparison between soybean and winter rape showed that soybean is a more suitable preceding crop for wheat than winter rape, significantly increasing the grain and straw yield of wheat [ 57 ]. Unfortunately, in the Czech Republic, winter rape is the dominant crop preceding wheat due to the high demand from the food and energy industries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, not only high yield is important, but also the favourable quality parameters of the grain. Selecting an appropriate position in the crop rotation and suitable agronomical management contribute to achieving this purpose (Gaweda & Haliniarz 2021). The optimization of the yield and quality of winter wheat grain depends not only on a suitable crop rotation but also on nitrogen fertilisation, which affects the biomass, accumulation, and distribution of nitrogen into the particular parts of the plants (Zhou et al 2013).…”
mentioning
confidence: 99%
“…audzēja pēc zirņiem un graudaugiem (Rosenberger et al, 2001). Kviešu graudi ar augstāku proteīna saturu, audzējot tos pēc sojas, salīdzinot ar ziemas rapsi kā kviešu priekšaugu, iegūti arī pētījumā Polijā, tomēr šīs būtiskās atšķirības starp proteīna saturu atkarībā no priekšaugiem vidēji bija tikai 0.4% robežā (13.0 % pēc sojas, 12.6% pēc ziemas rapša) (Gawęda, Haliniarz, 2021). Augu maiņas pozitīvo ietekmi uz augsnes fizikālajām, ķīmiskajām un bioloģiskajām īpašībām var papildināt, iekļaujot tajā sedzējaugus un samazinot augsnes apstrādes intensitāti (Zegada-Lizarazu, Monti, 2011).…”
Section: Augu Maiņa Kā Laukaugu Produktivitāti Veicinošs Faktorsunclassified
“…Polijā ziemas kviešu divfaktoru izmēģinājumā ar divām augsnes apstrādes sistēmām (TA un BA) un diviem kviešu priekšaugiem secināts, ka produktīvo stiebru skaits bija augstāks TA variantā, bet 1000 graudu masa un tilpummasa kviešu graudiem bija būtiski augstāka BA variantā. Novērots, ka garāki augi bijuši tradicionālās apstrādes variantā, kas nodrošināja arī būtiski augstāku salmu ražu, tomēr vidējā graudu raža starp augsnes apstrādes sistēmām būtiski neatšķīrās (Gawęda, Haliniarz, 2021).…”
Section: Augsnes Apstrādes Sistēmas Un To Ietekme Uz Kultūraugu Produ...unclassified
See 1 more Smart Citation